Increased Standardised Incidence Ratio of Malignant Pleural Mesothelioma in Taiwanese Asbestos Workers: A 29-Year Retrospective Cohort Study. (28th July 2015) - Lin, Cheng-Kuan; Chang, Yu-Ying; Wang, Jung-Der; Lee, Lukas Jyuhn-Hsiarn
Abstract : Objective . This paper aimed to determine the standardised incidence ratio (SIR) of malignant pleural mesothelioma (MPM) in workers exposed to asbestos in Taiwan. Methods . All workers employed in asbestos-related factories and registered by the Bureau of Labour Insurance between 1 March, 1950, and 31 December, 1989, were included in the study and were followed from 1 January, 1980, through 31 December, 2009. Incident cases of all cancers, including MPM (ICD-9 code: 163), were obtained from the Taiwan Cancer Registry. SIRs were calculated based on comparison with the incidence rate of the general population of Taiwan and adjusted for age, calendar period, sex, and duration of employment. Results . The highest SIR of MPM was found for male workers first employed before 1979, with a time since first employment more than 30 years (SIR 4.52, 95% CI: 2.25–8.09). After consideration of duration of employment, the SIR for male MPM was 5.78 (95% CI: 1.19–16.89) for the workers employed for more than 20 years in asbestos-related factories. Conclusions . This study corroborates the association between occupational asbestos exposure and MPM. The highest risk of MPM was found among male asbestos workers employed before 1979 and working for more than 20 years in asbestos-related factories.